Kinerja Pembangunan Daerah Berdasarkan Indeks Pembangunan Manusia - Purnomo, Didit; Utami, Diyan; Slamet Sukardi, Agung (Prosiding University Research Colloquium, 2021)
The Human Development Index (HDI) is one of the parameters used to measure development success. HDI is measured based on the level of education, health and expenditure. Central Java Province has a lower HDI value compared to other provinces in Java and is lower than its national level and only superior to East Java. So that the sample used in this research is 35 regencies/cities in Central Java Province during 2015-2018. The type of data used is secondary data sourced from BPS Central Java and other sources related to research. The dependent variable in this study was the HDI and the independent variable consisted of poverty level, population, inflation, GRDP and regency/city minimum wages in Central Java Province. This study aims to see how the influence of the independent variables on the dependent variable using panel data analysis techniques through the best model selection test, namely the chow test and the hausman test. Where chosen the best regression results Fixed Effect Model which shows that the poverty level variable has a negative and significant effect on HDI, economic growth variables and district / city minimum wages have a positive and significant effect on HDI, while the population and inflation variables do not have a significant effect on HDI in Central Java Province.